Effects of repeated (NH₄)₂SO₄ application on sulfur pools in soil, soil microbial biomass, and ground vegetation of two watersheds in the Black Forest/Germany - Prietzel, Jörg; Weick, Corry; Korintenberg, Julia; Seybold, Gabriele; Thumerer, Thomas; Treml, Bernd (Plant and soil, 2001)
The effect of repeated (NH₄)₂SO₄ applications (3 × 700 kg ha⁻¹ in 1988, 1991, and 1994, respectively) on S pools in soil, soil microbial biomass, and ground vegetation was studied at two Norway spruce (Picea abies L. [Karst.]) sites in the Black Forest/Germany. In both eco-systems, most of the total S pool was located in the soil. The soil also was the predominant compartment for retention of applied SO₄²⁻-S. The fractions of organic and inorganic S forms in the initial soil S content, and the retention of experimentally applied S was different for both sites. In the podzol Schluchsee, organic S accounted for 92% of total S. In the cambisol Villingen, the S pool consisted of 33% organic S and 67% inorganic S. The retention of applied S in various compartments of both ecosystems reflected these proportions. Only minor amounts of fertilized S (<1%) was retained in the spruce trees, ground vegetation, and soil microbial biomass. However, between 51% (Villingen) and 72% (Schluchsee) of the applied S was retained in the soil. In the Schluchsee podzol, 75% of retained fertilizer S was accumulated as ester sulfate, whereas SO₄²⁻ adsorption and precipitation of Al hydroxy sulfates were restricted by dissolved organic matter in the soil solution. In the Villingen cambisol, SO₄²⁻ adsorption was the dominant process of S retention, although 20% of the fertilized S again was retained as ester sulfate. The significant relevance of organic S forms in the retention of fertilizer S in both soils emphasizes the need for models which include the formation and remineralization of organic S compounds, especially of ester sulfates, for correctly simulating and predicting the retention and remobilization of S in acid forest soils subject to changing atmospheric N and S deposition.